Scoping studies of shielding to reduce the shutdown dose rates in the ITER ports. (1st June 2018) - Juárez, R.; Guirao, J.; Pampin, R.; Loughlin, M.; Polunovskiy, E.; Le Tonqueze, Y.; Bertalot, L.; Kolsek, A.; Ogando, F.; Udintsev, V.; Walsh, M.
Abstract: The planned in situ maintenance tasks in the ITER port interspace are fundamental to ensure the operation of equipment to control, evaluate and optimize the plasma performance during the entire facility lifetime. They are subject to a limit of shutdown dose rates (SDDR) of 100 µ Sv h −1 after 10 6 s of cooling time, which is nowadays a design driver for the port plugs as well as the application of ALARA. Three conceptual shielding proposals outside the ITER ports are studied in this work to support the achievement of this objective. Considered one by one, they offer reductions ranging from 25% to 50%, which are rather significant. This paper shows that, by combining these shields, the SDDR as low as 57Δ µ Sv h −1 can be achieved with a local approach considering only radiation from one port (no cross-talk form neighboring ports). The locally evaluated SDDR are well below the limit which is an essential pre-requisite for achieving 100 µ Sv h −1 in a global analysis including all contributions. Further studies will have to deal with a realistic port plug design and the cross-talks from neighbour ports.